Traumatic irreducible dislocation of the fifth metatarsophalangeal joint in pediatrics: case report and clinical experience - Li, Wen Chao; Liu, Li; Chen, Hui; Wang, Zhen Dong; Zhou, Hui Xia (Frontiers in Pediatrics, 2024)
Most of the dislocation of MTPJ could be closed reduction. However, isolated traumatic irreducible dislocation of the fifth MTPJ is an extremely rare injury, particular in child. We reported a case of 10-year-boy with irreducible dislocation of the fifth MTPJ who present by a dorsiflexion injury of the right foot 1 year ago. The attempt of closed reduction was performed with the failure of result. Computer Tomography (CT) showed that the dorsolateral dislocation of the fifth MTPJ. We performed the open reduction and metatarsal bone osteotomy with the short osteotomy about 0.8 cm. The osteotomy was adjusted to reduction of MTPJ and fixation by lock compression plate. The distal of growth plate in metatarsal bone was protected in avoid of pre-closure of growth plate. There were no instance of dislocation or signs of avascular necrosis of head of metatarsal bone. The results of this study demonstrated that open reduction and metatarsal bone osteotomy could be an optional treatment in the irreducible dislocation of the fifth MTPJ in children. We should pay more attention to the distal of growth plate in metatarsal bone in avoid of pre-closure of growth plate.